Effect of displacer on performance of Stirling-type pulse tube refrigerator with work recovery. (28th May 2021) - Zheng, Pu; Chen, Xi; Zeng, Yangping; Wu, Weidong; Wu, Yinong
Abstract : The displacer-type pulse tube refrigerator is a kind of Stirling-type pulse tube refrigerator with work recovery. It uses a displacer as a phase shifter and has the advantages of high efficiency and compact structure. One-dimensional numerical simulation of the displacer-type pulse tube refrigerator is performed, and the accuracy of the simulation is experimentally verified. The parametric analyses of displacer diameter, rod diameter, moving mass, spring stiffness, mechanical damping, and clearance seal are conducted. The results show that regenerator phase relations and work recovery effectiveness are significantly influenced by the displacer parameters, which further affect the performance. Regenerator phase relations and work recovery effectiveness are better when the rod diameter ratio to displacer diameter is about 0.5, contributing to the maximum coefficient of performance (COP c ). The rod diameter corresponding to the optimal cooling capacity is greater than that corresponding to the optimal COP c at the same displacer diameter. The length of the clearance seal has a slight effect on the performance when the height is less than 25 μm. Work recovery effectiveness is a unique attribute of the work recovery pulse tube refrigerator. Work recovery and phase shift require coupled analysis to optimize the performance of displacer-type pulse tube refrigerator.